Structure and Functions of the Gut Microbiome - Panda, Suchita; Guarner, Francisco; Manichanh, Chaysavanh (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2014)
Over the last decade our understanding of human gut microbiology underwent a tremendous transformation. The limitations of culture-based methods have given way to Next Generation Sequencing techniques, allowing us to understand the microbial gut community in greater depth. The human GI-tract harbours one of the most complex and abundant ecosystems colonized by more than 100 trillion microorganisms, among which Firmicutes and Bacteroidetes are the major phyla. Although stable over long periods, the composition and functions of the microbiome may be influenced by a number of factors including genetics, mode of delivery, age, diet, geographic location and medical treatments. Dysbiosis, changes in microbiome structure, has been linked to inflammatory, functional and metabolic disorders such as IBD, IBS and obesity. However, it is still not clear whether these changes are a contributing factor or a result of the disease. This synopsis provides a chronological overview of the techniques used to study the gut microbiota and the current knowledge with respect to the stability and variability of microbiome composition and functions.
Keywords: 16S rRNA